Restructuring MSMEs Businesses Through the Use of Digital Marketing as a Reflection on the Economic Impact of the Covid-19 Pandemic - Adawiyah, Rabi'atul; Adhitya, Fajar (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Micro, small and medium enterprises (MSMEs) are most affected by the Covid-19 pandemic. Therefore, the role of MSMEs is very strategic as it reduces unemployment and poverty in Indonesia, thus providing solutions to economic and social problems. This study analyzes efforts in rescuing MSMEs to maintain the stability of the national financial system affected by the Covid-19 pandemic. The study uses a qualitative descriptive approach with literature review and interviews. The interview's outcome was conducted to 100 MSMEs in Semarang City, Demak Regency and Kendal District shows the issues faced by MSMEs due to the Covid-19 pandemic are decreased sales and difficulty obtaining raw materials, business capitals and paying premises rents, also production and distribution disruption. The study concluded seven strategies for maintaining and increasing MSME sales: transforming its marketing and sales online, diverting products/services line, reallocation of the fund, hygiene, and halal assurance, providing vouchers or gift cards, accelerating asset sales, and reduction of labor. These seven scenarios are expected to encourage MSMEs to improve and develop their capacities to play the role of economic safety nets. However, the results of this study have limitations for MSMEs in areas that are still limited by internet networks, so that they have difficulty implementing digital-based marketing strategies.